PENDIDIKAN MILITER: Pendidikan Prioritas Pada Masa Turki Usmani - AUFA MAULIA ISTIADZAH; AFFA AULIA; LULU THUKMAIDAH PAKPAHAN; ELISA ANDRIYANTI; NURJANAH 1 (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2024)
Military education has a very important role in shaping a country's identity and combat readiness. This research explores the context of military education during the Ottoman Empire, focusing analysis on the strategy, role and impact on the sustainability of the Ottoman military's educational strength. The main aim of this research is to explore how the Ottoman Turkish military education system played a key role in forming a strong military identity, increasing the combat readiness of troops, and influencing the social structure and culture of society. Research methods involve in-depth analysis of relevant historical documents, literature, and primary sources. The aim of this research is to identify and analyze how the military education system during the Ottoman period played an important role in forming a strong military identity in terms of evaluating the military education curriculum, military strategy and the role of military education in producing effective military leaders among troops and Ottoman Turkish society. The long history of the Ottoman Turkish dynasty led by several leaders resulted in different types of leadership, including differences in policy decisions that occurred at that time. Both in the social, political, educational and military fields. As a nation with military blood, education during this kingdom era was largely concentrated on military training education, thus giving birth to the Yenissari army and making this country have a formidable war machine. It is hoped that the research results will provide deeper insight into the contribution of military education to Ottoman military power and how its influence penetrated the social and cultural structure of society at that time. This discovery can not only contribute to understanding the history of the Ottoman Empire, but also contribute to thinking regarding military education in the context of history and military development in general.